2022
DOI: 10.1038/s41388-022-02290-1
|View full text |Cite
|
Sign up to set email alerts
|

Malignant peripheral nerve sheath tumor: models, biology, and translation

Abstract: Malignant Peripheral Nerve Sheath Tumors (MPNSTs) are aggressive, invasive cancer that comprise around 10% of all soft tissue sarcomas and develop in about 8–13% of patients with Neurofibromatosis Type 1. They are associated with poor prognosis and are the leading cause of mortality in NF1 patients. MPNSTs can also develop sporadically or following exposure to radiation. There is currently no effective targeted therapy to treat MPNSTs and surgical removal remains the mainstay treatment. Unfortunately, surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 245 publications
0
30
0
Order By: Relevance
“…Further study of molecular pathology is an effective way for diagnosis and treatment. In addition, the analysis of cancer stem cells and genetics in MPNSTs is helpful to design new treatment schemes ( 23 ). Spyra et al.…”
Section: Discussionmentioning
confidence: 99%
“…Further study of molecular pathology is an effective way for diagnosis and treatment. In addition, the analysis of cancer stem cells and genetics in MPNSTs is helpful to design new treatment schemes ( 23 ). Spyra et al.…”
Section: Discussionmentioning
confidence: 99%
“…MPNSTs represent about 5% of all sarcomas and may arise from a peripheral nerve or a pre-existing neurofibroma; in about 50% of cases, these tumors arise in the context of NF1, while in the remaining cases they appear to be sporadic (40% of cases) or associated with a previous history of radiation [ 1 , 4 , 6 , 73 , 74 , 75 ]. A significant number of the sporadic tumors arise in the deep soft tissues without any anatomic evidence of association with a peripheral nerve or pre-existing neurofibroma (soft tissue MPNST) [ 73 , 74 , 75 ]. The sporadic tumors usually occur in patients with an age ranging from 30 to 50 years, while the NF1-asociated tumors can manifest in younger patients, including in childhood [ 73 , 74 , 75 ].…”
Section: Malignant Peripheral Nerve Sheath Tumors (Mpnsts)mentioning
confidence: 99%
“…A significant number of the sporadic tumors arise in the deep soft tissues without any anatomic evidence of association with a peripheral nerve or pre-existing neurofibroma (soft tissue MPNST) [ 73 , 74 , 75 ]. The sporadic tumors usually occur in patients with an age ranging from 30 to 50 years, while the NF1-asociated tumors can manifest in younger patients, including in childhood [ 73 , 74 , 75 ]. The most common sites are the extremities, trunk, and head/neck region; among the major nerves involved, the sciatic nerve is the most common one, followed by the brachial and sacral plexuses and the paraspinal nerves.…”
Section: Malignant Peripheral Nerve Sheath Tumors (Mpnsts)mentioning
confidence: 99%
See 1 more Smart Citation
“…In advanced diseases, the response rates to cytotoxic chemotherapy were low. In our study, the poor survival of MPNST patients receiving LSS could be attributed to the agressivity of the disease, high recurrence, and lack of chemosensibility due to mutation of the NF1 gene ( 35 , 36 ). Moreover, the landmark analysis for survivors with advanced osteosarcomas of ≥1 year revealed no effect of LSS on survival, which indicated that patients could benefit from LSS only within 1 year after sarcoma diagnosis.…”
Section: Discussionmentioning
confidence: 66%